2020
DOI: 10.3390/ijerph17113829
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Dry Eye Disease after Surgery-Indicated Chronic Rhinosinusitis: A Population-Based Cohort Study

Abstract: We aim to evaluate the risk of dry eye disease (DED) occurrence in patients with surgery-indicated chronic rhinosinusitis (CRS) via the national health insurance research database in Taiwan. After exclusion, patients with a diagnostic code of CRS and had received functional endoscopic sinus surgery (FESS) were regarded as having surgery-indicated CRS and enrolled in the study group, then each patient in the study group was age- and gender-matched to four non-CRS patients that served as the control group. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Finally, we excluded a considerable number of patients with CHD treated with PCI during the matching process. Nonetheless, our sample size is not smaller than those in previous population-based studies [14,24]; hence, the influence of this limitation might be minimal.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, we excluded a considerable number of patients with CHD treated with PCI during the matching process. Nonetheless, our sample size is not smaller than those in previous population-based studies [14,24]; hence, the influence of this limitation might be minimal.…”
Section: Discussionmentioning
confidence: 93%
“…Chronic rhinosinusitis (CRS) is a chronic inflammatory disorder of the nasal and paranasal mucosa that often involves the formation of nasal polyps [13]. CRS had been demonstrated to be associated with several inflammatory diseases, including asthma and dry eye disease [13,14]. Moreover, Wang et al, reported that CRS patients were at higher risk for acute myocardial infarction occurrence [15].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Recently, gout was found to elevate the risk of DED development, with longer periods of gout causing higher rates of DED [27]. In terms of local inflammatory disease, the presence of chronic rhinosinusitis is correlated with subsequent DED occurrence after excluding the effect of multiple risk factors for DED [28]. This is because the orbital and ocular involvement in NPC progression can alter the ocular structure and cause proptosis in the majority of cases [14], and NPC itself or radiotherapy can lead to ocular damage and possible inflammation [3,29].…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye disease (DED) is a prevalent inflammatory eye disease and the incidence of DED reached 60 percent in the Japanese population of visual display terminal users [ 17 ]. Regarding the type of DED, evaporative DED presents with the excessive evaporation of the tear film from the ocular surface, which is related to meibomian gland dysfunction (MGD) and tear film instability [ 18 , 19 , 20 ]. Another common type of DED is aqueous-deficient DED, which features a lacrimal deficiency and a subsequently reduced tear menisci height and radius of curvature [ 19 ], and the previous literature has demonstrated the significant correlation between aqueous-deficient DED and inflammatory syndromes like Sjogren syndrome, rheumatic arthritis, and diabetes mellitus (DM) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%